Mineralogy and Geochemistry of Gems - Melfos, Vasilios (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Gems have been used in the manufacture of jewellery and as ornaments since antiquity. Considering gems, recent statistics have shown that about 15 billion Euros are annually at stake. Nowadays, gemmology, i.e., the study of gem materials, is one of the most expanding fields in the earth sciences, positioned between academia and industry. As an applied science, in gemmology, the instruments used should be non- or microdestructive, and their cost should be reasonable both in terms of equipment and time consumption. Gemmology can also be used contribute to the development of pure science and in some cases, destructive techniques may have to be used. Taking into account the fact that gems are albeit rarely available for scientific research, this compilation of 20 articles by around 100 researchers from over 30 different institutions situated in 20 countries from around the globe, presented in the Special Issue entitled "Mineralogy and Geochemistry of Gems", offers very good examples on the application of various methods for their study which will hopefully contribute to our better understanding of gem formation in general and will enhance scientific debates attracting more scientists from various disciplines to get involved in this field.